DLQI scores in vitiligo: reliability and validity of the Persian version - Aghaei, Shahin (BioMed Central, 2004)
BACKGROUND: The objective of this study was to translate and to test the reliability and validity of the 10-item Dermatology Life Quality Index (DLQI) questionnaire in Iranian patients with vitiligo. METHODS: Using a standard "forward-backward" translation procedure, the English language version of the questionnaire was translated into Persian (the Iranian official language) by two bilinguals. Seventy patients with vitiligo attending the Department of Dermatology, Saadi Hospital, Shiraz, Iran, were enrolled in this study. The reliability and internal consistency of the questionnaire were assessed by Cronbach's alpha coefficient and Spearman's correlation, respectively. Validity was performed using convergent validity. RESULTS: In all, seventy people entered into the study. The mean age of respondents was 28.3 (SD = 11.09) years. Scores on the DLQI ranged from 0 to 24 (mean ± SD, 7.05 ± 5.13). Reliability analysis showed satisfactory result (Cronbach's α coefficient = 0.77). There were no statistically significant differences between daily activity (DA) and personal relationship (PR) scale mean scores in generalized versus focal-segmental involvement in sufferers (P = 0.056, P = 0.053, respectively). There were also strong differences between the mean scores of the PR (personal relationship) scale with the involvement of covered only and covered/uncovered areas (P= 0.016) that was statistically significant in the second group. CONCLUSIONS: The study findings showed that the Persian version of the DLQI questionnaire has a good structural characteristic and is a reliable and valid instrument that can be used for measuring the effects of vitiligo on quality of life.